A revision of the genus Conanalus Tinkham, 1943 (Orthoptera: Tettigoniidae) - Shi, Fu-Ming; Mao, Shao-Li; Ou, Xiao-Hong (Zootaxa, 2008)
A key to species of Conanalus Tinkham is given. Generic diagnosis is revised again. Two species are described as new: Conanalus brevicaudus sp. nov. and Conanalus robustus sp. nov. from Yunnan, China. The type specimens are deposited in Museum of Hebei University, Baoding, China.